Beliefs About Medicines and Adherence to Treatment in Turkish Patients with Inflammatory Bowel Disease - Can, Güray; Yozgat, Ahmet; Tezel, Ahmet; Ünsal, Gülbin; Soylu, Ali Rıza (Turkish Journal of Gastroenterology, 2022)
Background: Although studies are investigating the perception and beliefs about treatment and adherence to treatment in different societies related to inflammatory bowel disease, there are no studies on this subject in Turkish people with different sociocultural structures. In our study, we aimed to evaluate the beliefs about treatment and its effect on adherence to treatment in the Turkish population with inflammatory bowel disease. Methods: In the study, the “Medication Adherence Report Scale” and “Beliefs about Medicines Scale” scales were used to evaluate the treatment compliance and perception and beliefs about treatment. Characteristics that could affect treatment compliance were evaluated by statistical analysis. Results: A total of 253 patients, 167 with ulcerative colitis and 86 with Crohn’s disease, were included in the study. The non-adherence rate to the treatment was found as 41.9% in ulcerative colitis and 24.4% in Crohn’s disease (P = .006). Intentional (29.3% in ulcerative colitis and 16.3% in Crohn’s disease [P = .031] and unintentional non-adherence to treatment (28.1% in ulcerative colitis, 16.3% in Crohn’s disease [P = .037] were significantly higher in ulcerative colitis than in Crohn’s disease. Female gender (odds ratio = 2.59, P = .005), low education level (odds ratio = 4.8, P = .015), distal involvement in ulcerative colitis (P = .014), and thoughts about the disease would last too soon in Crohn’s disease (odds ratio = 4.17, P = .049) were risk factors for non-adherence to treatment. Conclusion: The negative perception of treatment in inflammatory bowel disease affects adherence to the treatment. Considering some social factors that affect adherence to the treatment and taking measures to enhance the adherence to treatment will increase the success of treatment. Cite this article as: Can G, Yozgat A, Tezel A, Ünsal G, Soylu AR. Beliefs about medicines and adherence to treatment in Turkish patients with inflammatory bowel disease. Turk J Gastroenterol. 2022;33(9):743-750.